Financial Performance AnalysisBanking CompanyOn the Indonesian Stock Exchange - Fredy Olimsar; Nurmawati Mambuhu; Nurhikmah Sibua; Sri Wahyuningsih; Alfiana Alfiana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The success of a bank can be measured by the ability of the bank's fiscal work. By looking at the ability of a bank's fiscal work, it can be concluded whether the bank is in good condition or not. This research aims to dissect the fiscal work capabilities of banks listed on the Indonesia Stock Exchange for the 2019-2021 period based on the bank's liquidity level and solvency level. This research uses data analysis, a quantitative descriptive approach style and the data collection method used in this research is the validation method and the data studied is in the form of daily financial reports I-IV. The population used in this research is all banks registered on the IDX for the 2019-2021 period. The slice model used in this exploration is a deliberate slice system. The results of this research show that firstly, the fiscal work capacity of banks listed on the Indonesia Stock Exchange for the 2019-2021 period based on the level of liquidity as measured by the current ratio is good because it is suitable for paying current debts due to the minimum measurability of 2 times or 200. Second, The fiscal performance of banks listed on the Indonesia Stock Exchange for the 2019-2021 period based on the level of solvency as measured by the debt to equity ratio shows that the condition is not bad because the figure is above the minimum measure of 35.